Anti-neuroinflammatory effects of Hibiscus sabdariffa Linn. (Roselle) on Lipopolysaccharides-induced Microglia and neuroblastoma cells - Nor Fadilah Rajab; Siti Masitah Musa; Munirah Ahmad Munawar; Leong, Lek Mun; Heng, Kai Yen; Farah Wahida Ibrahim; Chan, Kok Meng (Penerbit Universiti Kebangsaan Malaysia, 2016)
Hibiscus sabdariffa Linn. (roselle) is a polyphenol rich fruit. This study aimed to identify the neuroprotective effect of roselle on LPS-induced cell proliferation and nitric oxide-induced free radical in microglia and neuroblastoma cells. MTT assay was used to identify the appropriate concentration of roselle and LPS for microglia and neuroblastoma cells proliferation study. Griess assay were used to determine the level of nitric oxide accumulated based on the reaction of Griess to estimate the activity of iNOS in nitric oxide production. The results showed that roselle at the concentration of 50 μg/mL and 100 μg/mL and LPS at concentration of 1 μg/mL does not give cytotoxic effect towards microglia C8-B4 and neuroblastoma LN18 cells. The roselle treatment at 50 μg/mL and 100 μg/mL showed a protective effect on LPS-induced microglia C8-B4 cells. However, in neuroblastoma LN18 cells, no protective effect was seen on both 50 μg/mL and 100 μg/mL of roselle treatment following induction with 1 μg/mL of LPS. On the other hand, the production of nitric oxide (NO) was reduced when LPS-induced microglia C8-B4 cells were treated with 50 μg/mL of roselle. Treatment of roselle at concentration 100 μg/mL on LPS-induced neuroblastoma LN18 cells also reduced the production of nitric oxide. As a conclusion, roselle had the ability to give neuroprotective effect by the inhibition of LPS induction activity on microglia activation for normal and cancer cells at different concentrations.